Analysis of mortality in colorectal surgery in the Bi‐National Colorectal Cancer Audit. Issue 6 (18th April 2016) - Teloken, Patrick Ely; Spilsbury, Katrina; Platell, Cameron; ,
Abstract : Background: In the last decade, there has been a significant increase in interest for public reporting of outcome data and performance comparison across institutions and surgeons. This study aims at comparing postoperative mortality after colorectal cancer surgery across units and individual consultants in Australia and New Zealand using funnel plots. Methods: The Bi‐National Colorectal Cancer Audit database was used. Unadjusted and adjusted funnel plots of inpatient mortality were constructed. Risk adjustment was based upon multivariable logistic regression models using purposeful covariate selection. Results: A total of 10 008 patients undergoing surgery for colorectal cancer from 56 surgical units and 90 consultants were identified. Overall inpatient mortality was 1.51%, corresponding to 1.1% for elective and 3.9% for urgent cases. Logistic regression identified age, American Society of Anesthesiologists score, urgent surgery and open surgery to be independently associated with inpatient mortality. Unadjusted and adjusted funnel plot analysis identified three (5.3%) units exceeding the inner limit and none exceeding the outer limit. Six (6.6%) consultants had inpatient mortality between the upper inner and outer limits and one (1.1%) between the inferior inner and outer limits. Upon adjustment, seven (7.7%) consultants had inpatient mortality between the inner and outer limit. Potential limitations of this study include: residual confounding being responsible for the association of open surgery and mortality; incomplete case‐mix adjustment resulting in outlier identification; and bias towards inclusion of larger institutions. Conclusion: Mortality figures in Australia and New Zealand are comparable to recently reported international data. The vast majority of units and consultants are performing within the expected boundaries.